Whole genome CRISPRi screening identifies druggable vulnerabilities in an isoniazid resistant strain of Mycobacterium tuberculosis - XinYue Wang; William J. Jowsey; Chen-Yi Cheung; Caitlan J. Smart; Hannah R. Klaus; Noon EJ Seeto; Natalie JE Waller; Michael T. Chrisp; Amanda L. Peterson; Boatema Ofori-Anyinam; Emily Strong; Brunda Nijagal; et al. (Nature Communications)
Abstract Drug-resistant strains of Mycobacterium tuberculosis are a major global health problem. Resistance to the front-line antibiotic isoniazid is often associated with mutations in the katG-encoded bifunctional catalase-peroxidase. We hypothesise that perturbed KatG activity would generate collateral vulnerabilities in isoniazid-resistant katG mutants, providing potential pathway targets to combat isoniazid resistance. Whole genome CRISPRi screens, transcriptomics, and metabolomics were used to generate a genome-wide map of cellular vulnerabilities in an isoniazid-resistant katG mutant strain of M. tuberculosis. Here, we show that metabolic and transcriptional remodelling compensates for the loss of KatG but in doing so generates vulnerabilities in respiration, ribosome biogenesis, and nucleotide and amino acid metabolism. Importantly, these vulnerabilities are more sensitive to inhibition in an isoniazid-resistant katG mutant and translated to clinical isolates. This work highlights how changes in the physiology of drug-resistant strains generates druggable vulnerabilities that can be exploited to improve clinical outcomes.